2012
DOI: 10.3892/or.2012.2006
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor potentiates differentiation induction by all-trans retinoic acid and arsenic trioxide and enhances arsenic uptake in the acute promyelocytic leukemia cell line HT93A

Abstract: Abstract. The effects of arsenic trioxide (ATO), all-trans retinoic acid (ATRA) and granulocyte colony-stimulating factor (G-CSF), alone or in combination, were investigated by focusing on differentiation, growth inhibition and arsenic uptake in the acute promyelocytic leukemia (APL) cell line HT93A. ATO induced differentiation at low concentrations (0.125 µM) and apoptosis at high concentrations (1-2 µM). Furthermore, ATRA induced greater differentiation than ATO. No synergistic effect of ATRA and ATO was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…The induction of the granulocytic differentiation of leukemic cells by ATRA has been a major breakthrough in terms of survival for acute promyelocytic leukaemia (APL) patients [17]. In our study we reported that DNMTI procaine alone did not induce G-CSF expression, but in the combined treatment with ATRA enhanced G-CSF expression compared with ATRAtreatment.…”
Section: Conflict Of Interestsupporting
confidence: 47%
“…The induction of the granulocytic differentiation of leukemic cells by ATRA has been a major breakthrough in terms of survival for acute promyelocytic leukaemia (APL) patients [17]. In our study we reported that DNMTI procaine alone did not induce G-CSF expression, but in the combined treatment with ATRA enhanced G-CSF expression compared with ATRAtreatment.…”
Section: Conflict Of Interestsupporting
confidence: 47%
“…Morphological changes such as condensation of chromatin, lobulation of nuclei, and the expression profiling of surface markers have been used as markers of the differentiation of APL cells [15,81,85]. Consistent with previous findings, we have recently demonstrated that 0.125 μM ATO also induced differentiation in HT93A cells, another t(15;17)-positive APL cell line established from the peripheral blood of a patient with APL [86], as evidenced by the appearance of jelly-bean-shaped nuclei in almost all cells, accompanied by a significant increase in CD11c and CD15 expression [87]. Furthermore, we demonstrated that As 2 S 2 induced granulocyte differentiation in HL-60 cells, as evidenced by the increment in CD11b expression, in which oxidative stress associated with GSH depletion and p38 mitogenactivated protein kinase (MAPK) activation was involved [77,84].…”
Section: Differentiation Inductionsupporting
confidence: 87%
“…For morphological assessment, cytospin preparations of treated cells stained with Wright-Giemsa were evaluated by light microscopy as previously described (24). Furthermore, the numbers of cells with differentiation-associated morphological changes such as apparent lobulated nuclei, multi-lobulated nuclei were counted and presented as the percent of differentiated cells.…”
Section: Differentiation Analysis Differentiation Induction Was Confmentioning
confidence: 99%
“…Furthermore, the numbers of cells with differentiation-associated morphological changes such as apparent lobulated nuclei, multi-lobulated nuclei were counted and presented as the percent of differentiated cells. Myeloid maturation with cell surface marker was analyzed by FACSCanto flow cytometer (BD Immunocytometry System) using antibodies for CD11b and CD10 as previously described with minor modifications (24). In brief, approximately 1x10 6 cells were washed with PBS containing 2.5% FBS and 0.5% NaN 3 (PBSF) and stained with PE-conjugated mouse anti-human CD11b IgG or FITC-conjugated mouse anti-human CD10 IgG for 30 min at 4˚C in the dark.…”
Section: Differentiation Analysis Differentiation Induction Was Confmentioning
confidence: 99%
See 1 more Smart Citation